Exclusive J/[psi] photoproduction off protons in ultraperipheral p-Pb collisions at √sNN=5.02 TeV - Abelev, Betty; Angelov, Venelin; Busch, Oliver; Glässel, Peter; Klein, Jochen; Leardini, Lucia; Lohner, Daniel; Lu, Xianguo; Maire, Antonin; Mercado Pérez, Jorge; Oyama, Ken; Pachmayer, Yvonne C.; et al. (Physical review letters, 2014)
We present the first measurement at the LHC of exclusive J/ψ photoproduction off protons, in ultraperipheral proton-lead collisions at √sNN=5.02 TeV. Events are selected with a dimuon pair produced either in the rapidity interval, in the laboratory frame, 2.5<y<4 (p−Pb) or −3.6<y<−2.6 (Pb−p), and no other particles observed in the ALICE acceptance. The measured cross sections σ(γ+p→J/ψ+p) are 33.2±2.2(stat)±3.2(syst)±0.7(theor) nb in p−Pb and 284±36(stat)+27−32(syst)±26(theor) nb in Pb−p collisions. We measure this process up to about 700 GeV in the γp center of mass, which is a factor of two larger than the highest energy studied at HERA. The data are consistent with a power law dependence of the J/ψ photoproduction cross section in γp energies from about 20 to 700 GeV, or equivalently, from Bjorken x scaling variable between ∼2×10−2 and ∼2×10−5, thus indicating no significant change in the gluon density behavior of the proton between HERA and LHC energies.
*ALICE Collaboration: B. Abelev, V. Anguelov, O. Busch, P. Glässel, J. Klein, L. Leardini, D. Lohner, X.-G. Lu, A. Maire, J. Mercado Pérez, K. Oyama, Y. Pachmayer, F. Reidt, K. Reygers, R. Schicker, J. Stachel, J. Stiller, S. Vallero, M. Völkl, J. Wilkinson, B. Windelband, M. Winn, A. Zimmermann [und 927 weitere Personen]
Im Titel ist "psi" als griechischer Buchstabe dargestellt
Im Titel steht der Ausdruck "sNN" unter dem Wurzelsymbol, "NN" ist dabei tiefgestellt
Im Titel ist der Buchstabe s hochgestellt
Gesehen am 06.10.2020